Evaluation of change-of-direction movements in young rugby players - Condello, G.; Minganti, C.; Lupo, C.; Benvenuti, C.; Pacini, D.; Tessitore, A. (International Journal of Sports Physiology and Performance, 2013)
The evaluation of change-of-direction (COD) performance is strongly focused on the time spent to perform the test trials, while much less is known about the technical execution adopted during the COD movements. Thus, the purposes of this study were to evaluate (1) the relationship between straight- and COD-sprint tests and (2) the technical execution of COD movements in relation to different age categories of young rugby players. Young rugby players (N = 157, age range 8-19 y) completed a test battery composed of a 15-m straight-sprint test (15SS) and a 15-m sprint test performed with 2 changes of direction (15COD). Significant differences were detected between age categories for both tests. Significant correlations were found between 15SS and 15COD. The analysis of the technical execution of the 15COD test showed differences between age categories, with a prevalence of rounded turns up to the U15 category. These findings confirmed the relationship between straight and COD abilities in young male rugby players. Moreover, the new approach introduced by this study, based on the analysis of COD technical execution, revealed that this performance could be conditioned by the age and mastery level of the players.